Cardioactive and Antihypertensive Properties of Tinospora crispa: An In vivo Approach - Anjum, Juhaer; Aktar, Fahima; Chowdhury, Jakir Ahmed; Chowdhury, Abu Asad; Kabir, Shaila; Sikder, Md Al Amin; Amran, Md Shah (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Tinospora crispa, a potent medicinal plant with multiple clinical indications, has a recorded history of ethnopharmaceutical use as an antihypertensive and has also been reported for its cardioactive properties. The antihypertensive and cardioactive properties of the plant were investigated in two different animal models of hypertension (ethanol-induced and digoxin-induced). In both models, the plant’s ethanolic extract was observed to exert a dose-dependent effect. Furthermore, treatment with the ethanolic extract resulted in no undesirable changes in liver and kidney function parameters such as serum SGOT, SGPT and creatinine levels. The ethanolic extract of the plant may, therefore, be considered safe and effective for the treatment of hypertension, although further extensive research into this is warranted. Dhaka Univ. J. Pharm. Sci. 23(1): 1-6, 2024 (June)